2023
DOI: 10.1007/s00066-023-02132-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive geriatric assessment predicts radiation-induced acute toxicity in prostate cancer patients

Katarzyna Paal,
Bettina Stranz,
Eva-Maria Thurner
et al.

Abstract: Purpose The purpose of the present prospective study was to evaluate the significance of geriatric conditions measured by a comprehensive geriatric assessment (GA) for the prediction of the risk of high-grade acute radiation-induced toxicity. Methods A total of 314 prostate cancer patients (age ≥ 65 years) undergoing definitive radiotherapy at a tertiary academic center were included. Prior to treatment, patients underwent a GA. High-grade toxicity was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Importantly, geriatric conditions may affect response to radiation and studies reported that comprehensive geriatric assessment (CGA) can help to predict the occurrence of acute radiation-induced toxicities for patients treated for PCa or Head and neck cancers ( 30 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, geriatric conditions may affect response to radiation and studies reported that comprehensive geriatric assessment (CGA) can help to predict the occurrence of acute radiation-induced toxicities for patients treated for PCa or Head and neck cancers ( 30 32 ).…”
Section: Discussionmentioning
confidence: 99%